Strain relaxation in thin Si₁-ₓ-yGeₓCy layers on Si substrates - Valakh, M.Ya.; Gamov, D.V.; Dzhagan, V.M.; Lytvyn, O.S.; Melnik, V.P.; Romanjuk, B.M.; Popov, V.G.; Yukhymchuk, V.O. (Functional Materials, 2006)
The possibility to obtain a heterosystem consisting of the upper partially strained and lower relaxed layers by gradient in situ doping of SiGe layers with carbon is considered. The properties of the as-grown and annealed (600 to 1000℃) samples have been studied by Raman spectroscopy and atomic force microscopy. The strain relaxation degree in the
as-grown layers as estimated from the Raman spectra amounts 50 % for Si₀.₇-ʸGe₀.₃Сʸ and 0 % for Si₀.₉-ʸGe₀.₁Сʸ. During the annealing, the strain has been found to be relaxed not homogeneously over the whole structure but in a layer-by-layer way. The segregation of carbon atoms is observed for both types of as-grown Si₁-ₓ-ʸGeₓСʸ layers in the near-substrate regions. Розглянуто можливiсть отримання вiдрелаксованих sige шарiв на кремнiєвiй пiдкладцi, що градiєнтно in situ легувалися вуглецем у процесi епiтаксiї. Використовуючи спектроскопiю комбiнацiйного розсiювання свiтла (КРС) та атомну силову мiкроскопiю, дослiджено властивостi вихiдних зразкiв та зразкiв пiсля термiчних обробок у дiапазонi температур 600-1000℃. Iз спектрiв КРС оцiнено ступiнь пластичної релаксацiї у вихiдному Si₀.₇-ʸGe₀.₃Сʸ (50 %) та Si₀.₉-yGe₀.₁Сʸ (0 %) шарах. Встановлено, що при вiдпалах релаксацiя напружень вiдбувається не однаково по всьому об'єму, а пошарово. В обох типах Si₁-ₓ-ʸGeₓСʸ шарiв на їх iнтерфейсах з Si пiдкладками вiдбувається сегрегацiя вуглецю. Рассмотрена возможность получения отрелаксированных sige слоев на кремниевой подложке, градиентно in situ легированных углеродом в процессе эпитаксии. Используя спектроскопию комбинационного рассеяния света (КРС) и атомную силовую микроскопию, исследованы свойства исходных образцов и образцов после термических обработок в диапазоне температур 600-1000℃. Из спектров КРС оценена степень пластической релаксации в исходном Si₀.₇-ʸGe₀.₃Сʸ (50 %) и Si₀.₉-ʸGe₀.₁Сʸ (0 %) слоях. Установлено, что релаксация напряжений при отжигах происходит не однородно по всему объему, а послойно. В обоих типах Si₁-ₓ-ʸGeₓСʸ слоев происходит сегрегация углерода на интерфейсах с Si подложками.